How Ultra-Orthodox (Haredi) Israeli Women Cope with Normative and Difficult Pregnancy and Childbirth Experiences. - Engelsman, Shimrit Prins; Huss, Ephrat; Cwikel, Julie (Nashim: A Journal of Jewish Women's Studies & Gender Issues)
Jewish Haredi (ultra-Orthodox) society is characterized by high fertility as part of what it sees as an inherent female identity. This article examines patterns of health behaviors and subjective experiences during pregnancy and childbirth among Israeli Haredi women, based on a qualitative study designed to investigate these phenomena within the Haredi cultural and social context. The research question of interest was: Given the importance of fertility and children in the Haredi population, how do women cope with normative pregnancy and childbirth experiences and with those that may be challenging, difficult or traumatic? Twenty Haredi women were interviewed, and the content of their interviews was analyzed. Six themes emerged that highlighted issues faced by Haredi women: social pressure to conceive; availability of social-communal resources for women after childbirth; seeking knowledge about reproductive health; medical practices and choices; traumatic experiences of reproductive events; and spiritual issues. These themes emphasized the unique characteristics of the Haredi woman's pregnancy and childbirth experiences. The findings point to the central role of the rabbi, religious faith and spirituality, considerations when using medical services and the importance of modesty as resources that help the women to navigate pregnancy and childbirth, which are seen as experiences that build identity among ultra-Orthodox women. Adverse reproductive events may lead to distress, but there is a reluctance to discuss them or seek treatment. The discussion integrates the findings with the current state of the literature, points to areas of change and adaptation and proposes practical recommendations that reflect the need to promote culturally sensitive reproductive health practices within the existing Israeli health care system.